X-Ray and Optical Polarization Aligned with the Radio Jet Ejecta in GX 339–4 - G. Mastroserio; B. De Marco; M. C. Baglio; F. Carotenuto; S. Fabiani; T. D. Russell; F. Capitanio; Y. Cavecchi; S. Motta; D. M. Russell; M. Dovčiak; M. Del Santo; et al. (The Astrophysical Journal Letters)
We present the first X-ray polarization measurements of GX 339–4. IXPE observed this source twice during its 2023–2024 outburst, once in the soft-intermediate state and again during a soft state. The observation taken during the intermediate state shows a significant (4 σ ) polarization degree P _X = 1.3% ± 0.3% and polarization angle θ _X = −74° ± 7° only in the 3–8 keV band. FORS2 at the Very Large Telescope observed the source simultaneously, detecting optical polarization in the B , V , R , and I bands (between ∼0.1% and ∼0.7%), all roughly aligned with the X-ray polarization. We also detect a discrete jet knot from radio observations with the Australia Telescope Compact Array taken later in time; this knot would have been ejected from the system around the same time as the hard-to-soft X-ray state transition, and a bright radio flare occurred ∼3 months earlier. The proper motion of the jet knot provides a direct measurement of the jet orientation angle on the plane of the sky at the time of the ejection. We find that both the X-ray and optical polarization angles are aligned with the direction of the ballistic jet.